Patronage of Śaivism and Other Religious Groups in Western India under the Dynasties of the Kaṭaccuris, Gurjaras and Sendrakas from the 5th to the 8th Centuries - Schmiedchen, Annette (Indo-Iranian journal, 2013)
Southern Gujarat and north-western Maharashtra constituted a highly contested region in the early medieval period, between the 5th and 8th centuries. The majority of the royal grants were in favour of Vedic Brahmins without any specific Śaiva, Vaiṣṇava, or other sectarian leanings, the rest in favour of Hindu temples. Whereas the Traikūṭakas had been Vaiṣṇavas, Kaṭaccuri Kṛṣṇarāja is described as ‘devoted to Paśupati’. Not only among the Kaṭaccuris, but also among the Gurjaras, Sendrakas, and Lāṭa Calukyas, there was a strong tendency to use the religious epithet paramamāheśvara, ‘worshipper of Śiva’, homogeneously. Individual Gurjara and Sendraka charters record endowments for the worship of Āśramadeva and Alaṅghyeśvara, and one prince of the Lāṭa Calukyas is said to have worshipped a religious mendicant whose name ended in °śivabhaṭṭāraka. But it was not before the 11th century that the epigraphic evidence for the institutionalization of Śaivism in the region increased remarkably.